Systematic literature review informing the 2022 update of the EULAR recommendations for the management of ANCA-associated vasculitis (AAV): part 1—treatment of granulomatosis with polyangiitis and microscopic polyangiitis - Sara Monti; David Jayne; Bernhard Hellmich; Gunnar Tomasson; Raashid Ahmed Luqmani; Beatriz Sanchez-Alamo; Jan Henrik Schirmer (RMD Open, 2023)
Objective To summarise and update evidence to inform the 2022 update of the EULAR recommendations for the management of antineutrophil cytoplasm antibody-associated vasculitis (AAV).Methods A systematic literature review (SLR) was performed to identify current evidence regarding treatment of AAV. PubMed, EMBASE and the Cochrane library were searched from 1 February 2015 to 25 February 2022. The evidence presented here is focused on the treatment of granulomatosis with polyangiitis and microscopic polyangiitis.Results 3517 articles were screened and 175 assessed by full-text review. Ninety articles were included in the final evidence synthesis. Cyclophosphamide and rituximab (RTX) show similar efficacy for remission induction (level of evidence (LoE) 1a) but RTX is more effective in relapsing disease (LoE 1b). Glucocorticoid (GC) protocols with faster tapering result in similar remission rates but lower rates of serious infections (LoE 1b). Avacopan can be used to rapidly taper and replace GC (LoE 1b). Data on plasma exchange are inconsistent depending on the analysed trial populations but meta-analyses based on randomised controlled trials demonstrate a reduction of the risk of end-stage kidney disease at 1 year but not during long-term follow-up (LoE 1a). Use of RTX for maintenance of remission is associated with lower relapse rates compared with azathioprine (AZA, LoE 1b). Prolonged maintenance treatment results in lower relapse rates for both, AZA (LoE 1b) and RTX (LoE 1b).Conclusion This SLR provides current evidence to inform the 2022 update of the EULAR recommendations for the management of AAV.